Biochemical Characterization of a New Subfamily of Unusual Pathogenic Fungal Lipoxygenases - Hill, S. Gage (East Carolina University)
Lipoxygenases (LOX) are a family of enzymes that catalyze the (per)oxidation of polyunsaturated fatty acids. Over the last 30 years, fungal lipoxygenases have drawn interest because of their potential role in plant pathogenesis. This family of LOXs is distinct from the canonical LOXs in plants and animals due to i) nature of their metal center, ii) formation of a unique bis-allylic product, iii) post-translation, N-linked glycosylation, and iv) secreted from their host organism and implicated in pathogenesis. To date, six fungal LOXs have been biochemically characterized. A recent bioinformatics study revealed a potential new subfamily of fungal lipoxygenases, which deviate from the six 'prototype' fungal LOXs. These so-called 'class II' fungal LOXs have a cysteine amino acid where an otherwise conserved leucine residue is found across all LOXs. The Leu is considered a "substrate clamp" and previous mutations of this residue to volume-reducing alanine are linked to impairment of enzyme activity. Currently, there is no biochemical data reported for these putative class II fungal LOX enzymes. Herein, we use a combination of biochemical characterization methods and protein modeling to analyze three representative class II LOXs. The enzymes were successfully isolated from yeast expression cultures but showed no enzyme activity. AI generated structural models coupled with circular dichroism spectroscopy suggest that these enzymes fold similarly to that of LOXs, including nearly identical primary coordination sphere residues. Metal analysis indicates that the proteins can accommodate manganese or iron, consistent with other LOXs. To understand the functional consequence of these non-conserved mutations, a Leu-to-Cys variant was prepared for a paradigm plant LOX from soybean seeds. This variant is catalytically impaired. The collective data indicates that the class II LOXs are not effective at LOX activity; their potential biochemical function is discussed.
Keywords: kinetics; Lipoxygenases; Enzymes; Pathogenic fungi